Effect of pulsed infrared radiation on fracture healing in rabbits - Yusof, Abdul Halim (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Fracture healing is a highly cotnplex regenerative process that is essentially a replay of developmental events. Although tnedical technology and orthopedic tnanagetnent have itnproved greatly in the past 30 years, son1e fracture healed poorly, others take a long time to heal and sotne results in nonunion Biophysical stin1ulation provides an interesting 11011 operative alternatives in tackling these probletns. Infrared radiation is another biophysical stin1ulation using far infrared radiation (wavelength 1500nn1-1 nun) which is said in resonance with the process to be norn1alized. Objective To cotnpare fracture healing in tibia of rabbit between a group given pulsed infrared radiation and another group allowed to undergo norn1al healing. Assess1nent are 1nade through radiological and histological analysis. Methodology Sixteen matured tnale rabbits were used A transverse osteoton1y were carried out over the left tibia diaphysis and they were divided equally into 2 groups of 8 rabbits each Group A - exposed to infrared radiation. Group B - norn1al healing.( control group) They were then sacrificed at three and six weeks for assessn1ent. CT scan of each san1ple were then carried out.Each specin1en ts scanned in anteroposterior and lateral in1age (scout view or topogran1). These ilnages will show the proxitnal and distal extension of the hard callus. These areas is then scan with a slice interval of O.S1nn1 and slice thickness of l.Onun. A three ditnension image is then reconstructed. The fracture callus (hard callus) volutne is then calculated The 30 images were first reconstructed. Using volutnetric calculation the callus volun1e is then 111easured.For histological assesstnent, the specitnen were first cut into 2 equal halves sagitally, along the tibial axis Representative smnple \:vere taken frotn each specilnen. After the usual process they \vere then stained using lletnatoxylin and Eosin stain and 1110unted on DPX. The sections were then exan1ined under n1icroscope for presence of endosteal and periosteal callus, the area of cartilage and also fracture line. Results: .. • • ·At 3 weeks all specilnen from both the nonnal healing and infrared radiation group showed callus formation that bridges the fracture line that For the callus volurne, at 3 weeks the infrared group does show a higher volu1ne (ahnosl double) but at 6 weeks the callus volume are aln1ost equal. At 3 weeks woven bone are seen bridging the fracture site in both group. In the normal healing group larger area of cartilage were observed as compared to the infrared group The fracture gap persisted with no intervening tissue in all the specimen except for one normal healing speci1nen that shows intervening fibrous tissue At 6 weeks, no area of cartilage is seen and woven bone were now seen in between the fracture gap in both the group. In the infrared group there were presence of acute inflrunmatory cells at both 3 and 6 weeks which were absent in the nonnal healing group Conclusion This study had shown that in the infrared group callus volun1e at 3 weeks are aln1ost double as con1pru·ed with the nonnal healing group.At 6 weeks both the groups does not showed any significant differences in tern1s of callus volutne. Hence it is shown that pulsed infrared radiation enhanced healing process in earJy stage of fracture healing.